Fucoidan alleviates high sucrose-induced metabolic disorders and enhances intestinal homeostasis through modulation of Notch signaling - Jian Liu; Weiqiang Xia; Qifang Wu; Ya Zhang; Yu Wu; Boyang Li; Fangyu Chen; Xueting Du; Siya Wu; Yue Yang; Yitian Gao; Mingjiang Wu; et al. (Journal of Advanced Research)
Introduction: The therapeutic potential of fucoidan (FUC), a natural polysaccharide, in metabolic disorders is recognized, yet its underlying mechanisms remain unclear. Methods: We conducted investigations into the therapeutic mechanisms of FUC sourced from Sargassum fulvellum concerning metabolic disorders induced by a high-sucrose diet (HSD), employing Drosophila melanogaster and mice models. Drosophila larvae were subjected to HSD exposure to monitor growth inhibition, reduced pupation, and developmental delays. Additionally, we examined the impact of FUC on growth- and development-related hormones in Drosophila. Furthermore, we assessed the modulation of larval intestinal homeostasis by FUC, focusing on the regulation of Notch signaling. In mice, we evaluated the effects of FUC on HSD-induced impairments in intestinal epithelial barrier integrity and gut hormone secretion. Results: FUC supplementation significantly enhanced pupal weight in Drosophila larvae and effectively countered HSD-induced elevation of glucose and triglyceride levels. It notably influenced the expression of growth- and development-related hormones, particularly augmenting insulin-like peptides production while mitigating larval growth retardation. FUC also modulated larval intestinal homeostasis by negatively regulating Notch signaling, thereby protecting against HSD-induced metabolic stress. In mice, FUC ameliorated HSD-induced impairments in ileum epithelial barrier integrity and gut hormone secretion. Conclusions: Our findings demonstrate the multifaceted therapeutic effects of FUC in mitigating metabolic disorders and maintaining intestinal health. FUC holds promise as a therapeutic agent, with its effects attributed partly to the sulfate group and its ability to regulate Notch signaling, emphasizing its potential for addressing metabolic disorders.